MISTIK SUNAN BONANG - Ulfah, Rokhmah (Jurnal THEOLOGIA, 2013)
Abstract: This article will explain the mystical teachings of Sunan Bonang. He is a member of the Board Walisongo, which has a major role in the process of Islamization in Java. In preaching Islam, he is not only a cultural approach, but by creating songs and gending; he is also very closely related to the mystical teachings. In a mystical concept, humans must do the cleaning him self well so that it can unite with God. Mystical of Sunan Bonang can not classified as pantheism, but rather based on the Shari'a. He emphatically stated that there was separation between God and man, not fused together so that it difficult to separate between them. His teachings are very common among Walisogo which is to up hold the Sufism teachings of Ahlu al-Sunnah wa al-JamÄâ€™ah. Abstrak: Artikel ini akan menguraikan ajaran mistik Sunan Bonang. Ia adalah salah satu anggota Dewan Walisongo, yang memiliki peran besar dalam proses islamisasi di Jawa. Iatidak hanya melakukan pendekatan kultural, menciptakan tembang dan gending-gending, tetapi ia juga sangat lekat dengan ajaran mistiknya. Dalam konsep mistiknya, manusia harus melakukan pembersihan diri dengan baik sehingga bisa bersatu dengan Tuhan. Mistik Sunan Bonang bukan tergolong pantheisme, tetapi lebih berdasarkan pada syariat. Ia dengan tegas menyatakan adanya pemisah antara Tuhan dan manusia, bukan lebur menjadi satu sehingga sulit memisahkan antara keduanya. Ajaran seperti ini sudah sangat umum di kalangan Walisogo yang memang memegang teguh ajaran tasawuf Ahlu al-Sunnah wa al-JamÄâ€™ah. Keywords: Mistik, Pantheisme, Syariat, Tuhan, Walisongo.